Determinants of forward-looking information disclosures among nonfinancial firms in an emerging economy - Igbinovia, Ikponmwosa Michael; Rapheal, Oluwaseun Joy (Universitas Padjadjaran, 2026)
The disclosure of Forward-looking information (FLI) is non-mandatory. The study investigates the determinants of FLI by examining specific corporate governance and firm-level variables known from disclosures literature to be core determinants of voluntary disclosures. The investigation relied on data from 29 non-financial listed companies in a developing country over the period 2018 to 2023. From a positivist philosophy, the study adopted a quantitative approach. The authors employed a comprehensive methodological approach, involving the use of Descriptive Statistics, Panel Correlation, Panel Hausman Test, and the Panel Random Effects Model (REM). A balanced panel of 174 firm year observations was used to ascertain the impact of corporate governance and firm level attributes which are the independent variables of the study. The findings reveal that board independence and board size have a negative impact on FLI, suggesting that greater board independence and larger boards may reduce the extent of FLI disclosures. Conversely, board gender diversity and board foreign directorship positively influence FLI, indicating that diverse and internationally experienced boards contribute to better FLI disclosures. Firm size and leverage are also positively associated with FLI. Interestingly, the study finds that profitability has a negative relationship with FLI, suggesting that more profitable firms may focus less on disclosing FLI. The study provides additional insight using Nigerian evidence on the drivers of FLI disclosures in a developing country context, where information assymetry is dominant and regulation is relatively weak.